KOORDINASI INSTANSI DALAM PELAKSANAAN PROGRAM REHABILITASI SOSIAL RUMAH TIDAK LAYAK HUNI KOTA SURABAYA - Yuananta Prihatanto (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2019)
Social rehabilitation of uninhabitable house is a construction program that needs community participation. It is conducted by social services in Surabaya and Poor family development unit. The study aims to describe and analyse institution coordination in the implementation of construction program for uninhabitable house. The theoretical framework uses coordination theory in Inu Kencana (2011) i.e. arrangement, synchronization, common interest, and common goals. This is a qualitative descriptive method and population sampling techniques are applied through observation, interview, and documentation. The results indicate that the indicators of arrangement, synchronization, and common goals are well applied in the implementation of social rehabilitation of uninhabitable house program in North Perak. Whereas, the indicator of common interest is not well applied. For this reason, the program should be evaluated regarding the disbursement of funds in the implementation of social rehabilitation of uninhabitable house.